Character Education-Based Physics Digital Comic for 12-14 Years Old Students - Megawati Ridwan Fitri; Antomi Saregar; Sri Latifah (Online Learning In Educational Research (OLER), 2022)
Character values must be instilled in students through unique learning media. Therefore, it is necessary to investigate and develop new learning media relevant to character education's current challenges. This research aimed to determine the feasibility of character education-based physics digital comics. The Research and Development method with Borg and Gall model was employed in this development research. The product was validated by two media experts, two material experts, one language expert, and one IT expert. The development of character education-based digital comics received a material expert validation score of 98.33%, a media expert validation score of 90.33%, a language expert validation score of 80%, and an IT expert validation score of 80%. The product is appropriate for physics learning based on the validation score. However, because the product developed was limited to KI-3, more research is needed to develop the comic to contain KI-4 (skills).